The Effects of Student Success Workshops on Undergraduate Hispanic STEM Students on the U.S.-Mexico Border - J. Elizabeth Casey; Runchang Lin; Selina V. Mireles; Rohitha Goonatilake (IAFOR Journal of Education, 2019)
The goal of the College of Arts & Sciences Community-aid (CASC-aid) project, a National Science Foundation grant funded study (2016-2021), is to develop, implement, and evaluate a program that fosters a community of academic success for Hispanic STEM students. This Hispanic Serving Institute continues to provide a variety of supports to safeguard success for Hispanic CASC-aid scholars through effective communication. Along with scholarships, Project CASC-aid delivers mentoring and intervention strategies related to non-cognitive behavioral practices to ensure scholars are motivated and empowered, and to support the postsecondary educational success of Hispanic students (Blackwell, Trzesniewski, & Dweck, 2007). Embedded within the research is a Formative Experiment (Reinking & Bradley, 2008), which allowed researchers to gather data on one facet of the project. CASC-aid scholars responded to surveys after Student Success Workshops held across the 2017-2019 academic years. Analysis of results demonstrated that workshops were effective in supporting students’ long-term goals, career major decisions, and overall knowledge of a wider STEM field.